2019
DOI: 10.1093/ofid/ofz043
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Preferences Regarding the Use of Rapid Self-Testing for Sexually Transmitted Infections and HIV in San Diego Area Men Who Have Sex With Men

Abstract: Background Sexually transmitted infections (STIs) increase the risk of HIV transmission and are present at high rates among men who have sex with men (MSM). Adherence to HIV/STI testing guidelines is low in the United States. Testing programs that utilize rapid self-administered HIV/STI tests improve testing rates, though multiple factors influence their uptake. Methods MSM were recruited at an HIV/STI testing and treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
0
27
2
Order By: Relevance
“…Many studies explored preference for HIVST compared with other testing modes. [54][55][56][57][58][59][60][61][62][63] Huang et al (2016) provided In a 2016 study of Black and Latino MSM who completed surveys before and after HIVST home delivery, 77% of respondents preferred or somewhat preferred HIVST compared to traditional clinic-based testing. 57 However, Freeman et al (2018) found that many participants saw HIVST mainly as an option to supplement but not replace their regular testing in clinics and overall preferred facility-based testing, and another study found social mediausing YMSM did not prefer HIVST over other testing options despite being generally favorable toward HIVST.…”
Section: Comparing Hivst To Clinic/ Community-based Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies explored preference for HIVST compared with other testing modes. [54][55][56][57][58][59][60][61][62][63] Huang et al (2016) provided In a 2016 study of Black and Latino MSM who completed surveys before and after HIVST home delivery, 77% of respondents preferred or somewhat preferred HIVST compared to traditional clinic-based testing. 57 However, Freeman et al (2018) found that many participants saw HIVST mainly as an option to supplement but not replace their regular testing in clinics and overall preferred facility-based testing, and another study found social mediausing YMSM did not prefer HIVST over other testing options despite being generally favorable toward HIVST.…”
Section: Comparing Hivst To Clinic/ Community-based Testingmentioning
confidence: 99%
“…The convenience of HIVST compared to testing in facilities was a value described by participants of many studies included in this review. 55,56,[58][59][60][61][62][63][64][65][66][67][68][69][70] Through focus groups and qualitative interviews of MSM, Freeman et al 2018found that the convenience of purchasing an HIV test and having the test available when needed was valuable to participants. Hubbard et al (2020) also reported that 52% of participants in their study liked that using HIVST allowed them to test at their own convenience.…”
Section: Conveniencementioning
confidence: 99%
See 3 more Smart Citations